Dengue hemorrhagic fever outbreak in children in Port Sudan - Amal Malik; Kenneth Earhart; Emad Mohareb; Magdi Saad; Mubarak Saeed; Ali Ageep; Atef Soliman (Elsevier, 2011)
Summary: Dengue fever (DF)/dengue hemorrhagic fever (DHF) has emerged as a global public health problem with countries in Asia and the Pacific sharing more than 70% of the disease burden. In 2004-2005 a total of 312 cases admitted to Pediatric and Sea Port Hospitals in Port Sudan were clinically diagnosed as DHF. The mortality rate recorded was 3.8% (n = 12). Of the cases 73.4% were patients 5-15 years of age. A total of 91.2% of cases were admitted during May and June 2005 with 49.4% residing in the eastern region of Port Sudan. Dengue shock syndrome was observed in 37 of 312 (11.9%). All patients had thrombocytopenia with platelets count ranged from <100,000 to <150,000 cell/mm3. Of the 40 sera tested using RAPID-cassette test in the Khartoum Central Public Health Lab, 36 (90%) were dengue IgM positive. A subset of these sera (n = 23) were sent to NAMRU-3 and confirmed by IgM-capture ELISA; 9 of 23 were PCR positive for dengue serotype 3. Keyword: Dengue Port-Sudan